Heterojunctions Based on Amorphous Silicon: A Versatile Surface Engineering Strategy to Tune Peak Position of Redox Monolayers on Photoelectrodes - Gonçales, V.R.; Lian, J.; Gautam, S.; Hagness, D.; Yang, Y.; Tilley, R.D.; Ciampi, Simone; Gooding, J.J. (AMER CHEMICAL SOC, 2020)
Heterojunctions are typically used to generate large photovoltages and to influence the direction of flow of charge carriers on photovoltaic and photocatalytic devices. Herein, we propose how heterojunctions can be used as a pathway for tuning the peak position of redox active monolayers. This was possible by exploring the principle of contact between materials in heterojunctions leading to a common equilibrium Fermi level for both sides of the heterojunction. The phenomenon was demonstrated with thin layers of intrinsic amorphous silicon deposited on platinum, indium tin oxide, and either n-type or p-type crystalline silicon electrodes. At fixed light-intensity conditions, the potential required for electron transfer of a model redox probe was modulated according to the substrate on which the amorphous silicon was deposited. This allowed us to alter the peak position of a redox process occurring on the electrolyte side of the junction despite it being isolated from the underlying conducting material. We show how such an effect can be explored in a potential range that encompasses any of the redox monolayers electroactive in aqueous electrolytes.